Assessment and prediction of chloride ingress and carbonation in patch repair mortars - Arito, Ezekiel (Concrete Materials and Structural Integrity Research Unit (CoMSIRU), 2017)
The specifications for concrete patch repair mortars usually entail mechanical properties such as compressive strength and tensile strength. However, these properties may not directly relate to the desired performance in relation to durability and prevention of reinforcement corrosion. In addition, the literature does not show any direct relationship between compressive strength and durability properties of concrete and mortars in natural exposure conditions. Relevant performance requirements, such as carbonation resistance and chloride resistance, are usually not considered despite the fact that they have a direct influence on the durability performance of concrete repair mortars. The widespread premature failure of patch repairs which meet the existing compressive strength criteria implies that the use of compressive strength as a performance indicator may not provide a reliable measure of the durability performance. Therefore it can be argued that modern concrete repairs should be based on durability considerations, rather than compressive strength. In this study, an experimental investigation was conducted to determine the durability performance of patch repair mortars. Experimental results were analysed to investigate the correlations that exist between (i) electrical conductivity (Chloride Conductivity Index test) and rate of chloride-ion diffusion (bulk diffusion test), and (ii) gas permeability (Oxygen Permeability Index test) and rate of carbonation (accelerated carbonation test) in patch repair mortars. Eight mortar mixes were used in the investigation, including four commercially available repair mortars and four laboratory-made mortar mixes. To vary the pore structure of the laboratory mixes, different water/binder ratios (0.45 and 0.60) and binder types (100% Portland cement and 50/50 blend of Portland cement/blast furnace slag) were used to make the mortar specimens. Two curing conditions (dry and moist) were adopted with the aim of investigating the influence of curing on durability performance of patch repair mortars. Test results indicate good correlations between electrical conductivity and rate of chloride diffusion (correlation coefficient of 0.9112), and between oxygen permeability and rate of carbonation (correlation coefficient of 0.6751). This correlation was mainly attributed to the fact that these material properties largely depend on the pore structure (specifically the size, connectivity and tortuosity of pores). The good correlation further implies that electrical conductivity and oxygen permeability of repair mortars as evaluated by the CCI and OPI tests may provide a reasonable measure of chloride resistance and carbonation resistance respectively. However, the prediction of chloride ingress and carbonation depth from the electrical and gas permeability properties respectively, ought to be implemented within the range where reasonable correlation can be established. The results also showed that the durability performance of repair mortars in terms of chloride and carbonation resistance is sensitive to material factors, such as w/b ratio, curing type and binder type, which directly influence penetrability. Service life models for predicting chloride ingress and carbonation in the patch repair mortars used in this study were developed based on modified Fickian equations. The prediction profiles for chloride penetration were developed from a modified solution to Fick's second law of diffusion, while the carbonation depth prediction profiles were developed from the square-root-of-time law. Chloride penetration and carbonation depth could be predicted using the developed profiles. Though several assumptions that should be verified and/or modified in future work were made, the modelling results of this study serve as useful framework for evaluating the resistance to chloride ingress and carbonation in patch repair mortars.